Pre-drying and submerged cap winemaking: Effects on polyphenolic compounds and sensory descriptors. Part II: BRS Carmem and Bordo (Vitis labrusca L.) - Machado de Castilhos, Mauricio Bonatto [UNESP] (2015)
Brazilian wine production is dominated by the use of American grape cultivars (Vitis labrusca L.) and their hybrids. In this context, this study analyzed the phenolic composition and sensory profile of Bordo and BRS Carmem red wines elaborated from traditional and two alternative winemaking technologies: grape pre-drying and submerged cap of chaptalized musts. Anthocyanins and pyranoanthocyanins apparently seemed to be affected by the thermal process (60 degrees C), causing their degradation. In addition, the decrease of the concentration of these compounds could be suggested as a result of possible oxidation and hydrolysis reactions of anthocyanin 3-glucosides. Stilbenes were also affected by thermal degradation; however, flavan-3-ols and HCAD seemed to be less affected by the drying process. Submerged cap winemaking resulted in an increase of the anthocyanin and pyranoanthocyanin compounds due to the constant contact between the must and pomace during the alcoholic fermentation. The antioxidant capacity seemed not to be affected by thermal degradation, since the products of Maillard reaction also present antioxidant properties. Pre-dried wines were described as structured due to their higher flavan-3-ols content, and with high color intensity probably due to the formation of Maillard reaction products. The submerged cap wines presented an intense violet hue due to their high anthocyanin derivative concentrations and showed strong correlation with all other classes of the phenolic compounds. (C) 2015 Elsevier Ltd. All rights reserved.